2017
DOI: 10.1038/s41598-017-09056-w
|View full text |Cite|
|
Sign up to set email alerts
|

Large spontaneous exchange bias in a weak ferromagnet Pb6Ni9(TeO6)5

Abstract: We report the magnetic and dielectric behavior of Pb6Ni9(TeO6)5, a new compound comprising the honeycomb-like layers of S = 1 spins, through detailed structural, magnetic and dielectric investigation. An antiferromagnetic-type transition at 25 K (T N) with weak-ferromagnetic behavior is revealed. Interestingly, a large value of coercive field of 1.32 T at 2 K is observed. The isothermal magnetization after zero-field-cooled condition, it exhibits the presence of large spontaneous exchange bias (SEB) with a mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As examples, it has been reported that Sr 4 FeRuO 8 and Sr 3 FeRuO 7 exhibits similar type of temperature dependence of magnetization with T N across 11 K and 23 K, respectively [16]. Koteswararao et al reported the presence of weak ferromagnetic moments in the antiferromagnetic state of Pb 6 Ni 9 (TeO 6 ) 5 which led to clear bifurcation between the ZFC and FC curves [17]. As noted in the Introduction, loose spins in Co 2 RuO 4 are likely due to Ru 3+ ions with spin S = 1/2 because of the weaker and random A-B coupling which we argue later is also the source of the SG state.…”
Section: Temperature Dependence Of Dc-magnetic Susceptibilitiesmentioning
confidence: 96%
“…As examples, it has been reported that Sr 4 FeRuO 8 and Sr 3 FeRuO 7 exhibits similar type of temperature dependence of magnetization with T N across 11 K and 23 K, respectively [16]. Koteswararao et al reported the presence of weak ferromagnetic moments in the antiferromagnetic state of Pb 6 Ni 9 (TeO 6 ) 5 which led to clear bifurcation between the ZFC and FC curves [17]. As noted in the Introduction, loose spins in Co 2 RuO 4 are likely due to Ru 3+ ions with spin S = 1/2 because of the weaker and random A-B coupling which we argue later is also the source of the SG state.…”
Section: Temperature Dependence Of Dc-magnetic Susceptibilitiesmentioning
confidence: 96%
“…Although nanostructured Mn‐doped MoS 2 with a grain size of a few nanometers has shown multiple magnetic phases, [ 12 ] this possibly originates from defects or Mn‐clustering in such a disordered system, thus hindering the potential applications for magnetic refrigeration cycles and exchange bias modulation. [ 15–18 ] To the best of our knowledge, no multiple magnetic phases in 2D single crystals have been reported. In this study, we explore the magnetic properties of Mn‐doped SnS 2 single crystals with different Mn‐doping concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In this context we became interested in phase formation studies of lead(II) oxotellurates that additionally contain divalent first‐row transition metal cations with unpaired electrons, because this may result in new (non‐centrosymmetric) compounds and with interesting magnetic properties, as exemplified by Pb 6 Ni 9 (TeO 6 ) 5 that crystallizes in space group type P 6 3 22 and shows a large spontaneous magnetic exchange bias . Focusing on lead(II) copper(II) oxotellurates, only three phases have been structurally characterized up to date in the Pb/Cu/Te/O system, viz.…”
Section: Introductionmentioning
confidence: 99%